People and places a 21st century atlas of the UK - Dorling, Daniel 1968-; Thomas, Bethan (Policy Press, 2023)
How has UK society changed since 2001? What does the UK population look like in 2016? This unique atlas, the third in a bestselling series, uses a wealth of up-to-the minute data sources alongside the last 2011 Census data to identify national and local trends and provide analysis and discussion of the implications of these for future policy. Fascinating information on everything from sex, age, marriage and ethnicity to qualifications, employment, housing and migration is provided in gloriously colourful maps and graphics